Widyaiswara Competency Development at the Center for Human Resources Development for Electricity, New, Renewable Energy and Energy Conservation (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
Widyaiswara is a training human resource who has a very important role for the training unit in the cycle of education and training. At the Human Resource Development Center for Electricity, New Energy, Renewable Energy and Energy Conservation (PPSDM KEBTKE). Competency development for Widyaiswara in the KEBTKE PPSDM unit is not optimal and still requires increased development. This study aims to analyze the implementation of competency development, competency factors that influence development, and formulate a development strategy that suits the needs of Widyaiswara in supporting the performance of the KEBTKE PPSDM Organization. This study uses descriptive qualitative research methodology by using research instruments in the form of interview guidelines and supporting documents. The results of this study indicate that Widyaiswara PPSDM KEBTKE requires an increase in work experience competencies through non-classical training in the form of internships can increase real experience in the field, develop skills, and improve the quality of work experience.